Building interventions when distress is under debate: a case study from Appalachia. (October 2019) - Snell-Rood, Claire; Jenkins, Ryan; Hudson, Keisha; Frazier, Carole; Noble, Wayne; Feltner, Frances
Scholarship on idioms of distress has emphasized cross-cultural variation, but devoted less attention to intra-cultural variation—specifically, how the legitimacy of distress may vary according to the context in which it is expressed, social position, and interaction with medical categories of distress. This variation can pose challenges for interventionists seeking to establish culturally acceptable ways of identifying distress and creating relevant resources for recovery. We describe efforts over three years (2014–2016) to identify and adapt a culturally appropriate evidence-based intervention for depressed rural Appalachian women. Though the prevalence of depression among rural women is high, limited services and social barriers restrict treatment access. Formative research revealed varied understandings of distress. Depression was (a) medicalized as a treatable condition, (b) stigmatized as mental illness, (c) accepted as a non-pathological reaction to regional poverty and gendered caregiving responsibilities, (d) rejected as a worthy justification for seeking individual care, and (e) less represented in comparison to other competing forms of distress (i.e., multiple morbidities, family members' distress). In a small pilot trial, we applied an implementation science perspective to identify and implement appropriate evidence-based programming for the context. We outline how we reached Appalachian women despite these diverse understandings of depression and established a flexible medicalization of depression that enabled us to legitimize care-seeking, work with varied rural healthcare professionals, and engender culturally relevant support. Our adaptation and implementation of the concept of "mental health recovery" enabled the development of programming that furthered non-pathological communicative distress while resisting the normalization that silences women in the context of deep health disparities.